Protease‐activated receptor signaling in intestinal permeability regulation. (23rd September 2019) - Pontarollo, Giulia; Mann, Amrit; Brandão, Inês; Malinarich, Frano; Schöpf, Marie; Reinhardt, Christoph
Abstract : Protease‐activated receptors (PARs) are a unique class of G‐protein‐coupled transmembrane receptors, which revolutionized the perception of proteases from degradative enzymes to context‐specific signaling factors. Although PARs are traditionally known to affect several vascular responses, recent investigations have started to pinpoint the functional role of PAR signaling in the gastrointestinal (GI) tract. This organ is exposed to the highest number of proteases, either from the gut lumen or from the mucosa. Luminal proteases include the host's digestive enzymes and the proteases released by the commensal microbiota, while mucosal proteases entail extravascular clotting factors and the enzymes released from resident and infiltrating immune cells. Active proteases and, in case of a disrupted gut barrier, even entire microorganisms are capable to translocate the intestinal epithelium, particularly under inflammatory conditions. Especially PAR‐1 and PAR‐2, expressed throughout the GI tract, impact gut permeability regulation, a major factor affecting intestinal physiology and metabolic inflammation. In addition, PARs are critically involved in the onset of inflammatory bowel diseases, irritable bowel syndrome, and tumor progression. Due to the number of proteases involved and the multiple cell types affected, selective regulation of intestinal PARs represents an interesting therapeutic strategy. The analysis of tissue/cell‐specific knockout animal models will be of crucial importance to unravel the intrinsic complexity of this signaling network. Here, we provide an overview on the implication of PARs in intestinal permeability regulation under physiologic and disease conditions. Abstract : The protease‐activated receptors (PAR)‐1 and PAR‐2 in the intestinal mucosa can be activated by numerous gut microbe and host proteases. These receptors are expressed throughout the gastrointestinal tract and impact gut permeability regulation, a major factor affecting intestinal physiology and metabolic inflammation. In this Viewpoint article, we provide an overview of the functional regulation of intestinal PARs under physiological and disease conditions.